Effective polysulfide trapping polar interlayer for high rate Li-S batteries - Karuppiah, Saravanan; Kalimuthu, Balakumar; Nazrulla, Mohammed Azeezulla; Krishnamurty, Sailaja; Nallathamby, Kalaiselvi (Journal of Materials Chemistry A, 2019)
A microporous and polymeric C3N4 framework (CNF), when exploited as an interlayer and as a cathode host in Li-S batteries, demonstrates significantly improved electrochemical behavior with a special relevance to high rate applications up to 5C. A CNF obtained through a template free synthesis approach and activated with KOH is endowed with a high specific surface area of 1000 m(2) g(-1), a desirable nitrogen content (13%) to ensure polarity and a microporous architecture, required to increase the accommodation capability of discharge products. The difference in electronegativity between C and N in CNFs combats in a major way the shuttling of lithium polysulfides (LIPSs) and ensures the realization of increased LIPS binding sites due to the presence of pyridinic nitrogen. Furthermore, a CNF driven change in the molecular configuration of adsorbed LIPSs leads to the uniform distribution and sequestration of discharge products. Similarly, micropores and the polymeric nature of CNFs facilitate the effective confinement of LIPSs and ably accommodate the volume changes (through the formation of Li2S upon discharge) respectively, especially when a microporous CNF interlayer is involved in the Li-S assembly. In particular, a CNF with 60 wt% sulfur loading, otherwise represented as CNFS-60, when exploited as a cathode in combination with the deployment of a CNF interlayer exhibits appreciable capacity values of 500 and 400 mA h g(-1) at 3 and 5C respectively. Furthermore, the combination of the CNF interlayer and cathode demonstrates a steady state discharge capacity of 437 mA h g(-1) at 1C rate up to 300 cycles, without any significant capacity loss. The involvement of chemical interaction of the CNF with lithium polysulfides is demonstrated using density functional theory calculations. Hence, the effective trapping and the subsequent localization of migrating LIPSs arising from the strong chemical interaction of the CNF with soluble LIPSs and the advantages of high concentration of accessible pyridinic nitrogen sites to the LIPS adsorption in improving the electrochemical behavior of the Li-S system could be understood. This new CNF based interlayer provides a promising approach and ample scope for its implementation in futuristic Li-S batteries.

Synthesis, characterization, pharmacological and computational studies of 4, 5, 6, 7-tetrahydro-1, 3-benzothiazole incorporated azo dyes - Maliyappa, M. R.; Keshavayya, J.; Mallikarjuna, N. M.; Krishna, P. Murali; Shivakumara, N.; Sandeep, Telkar; Sailaja, Krishnamurty; Nazrulla, Mohammed Azeezulla (Journal of Molecular Structure, 2019)
The present work describes the synthesis of five novel heterocyclic azo dyes (4a-4e) through conventional diazo-coupling reaction of 4, 5, 6, 7-tetrahydro-1, 3-benzothiazole with various coupling compounds at 0-5 degrees C. The chemical structures of the synthesized azo dyes were characterized by both theoretical and experimental techniques. All the synthesized molecules were evaluated for their antioxidant activity by two different techniques such as DPPH and FRAP. The results indicated that all the synthesized compounds proved to be potent antioxidants. The anti-mycobacterial activity of the azo dyes was tested against M. tuberculosis and the compounds 4a and 4e showed higher activity among the tested dyes. The DNA binding studies showed effective intercalation properties between the azo dyes and CT-DNA. Finally, the molecular docking studies indicated a possible interaction of the azo dyes with target receptor RpsA. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: Azo dyes; Benzothiazole; CT-DNA; DFT; tuberculosis

Unprecedented isomerism-activity relation in molecular electrocatalysis - Kottaichamy, Alagar Raja; Begum, Shabbah; Nazrulla, Mohammed Azeezulla; Dargily, Neethu Christudas; Devendrachari, Mruthyunjayachari Chattanahalli; Bhat, Zahid Manzoor; Thimmappa, Ravikumar; Kotresh, Harish Makri Nimbegondi; Vinod, Chathakudath Prabhakaran; Thotiyl, Musthafa Ottakam (Journal of Physical Chemistry Letters, 2020)
The role of electrocatalysts in energy storage/conversion, biomedical and environmental sectors, green chemistry, and much more has generated enormous interest in comprehending their structure-activity relations. While targeting the surface-to-volume ratio, exposing reactive crystal planes and interfacial modifications are time-tested considerations for activating metallic catalysts; it is primarily by substitution in molecular electrocatalysts. This account draws the distinction between a substituent's chemical identity and isomerism, when regioisomerism of the -NO2 substituent is conferred at the ``alpha'' and ``beta'' positions on the macrocycle of cobalt phthalocyanines. Spectroscopic analysis and theoretical calculations establish that the beta isomer accumulates catalytically active intermediates via a cumulative influence of inductive and resonance effects. However, the field effect in the alpha isomer restricts this activation due to a vanishing resonance effect. The demonstration of the distinct role of isomerism in substituted molecular electrocatalysts for reactions ranging from energy conversion to biosensing highlights that isomerism of the substituents makes an independent contribution to electrocatalysis over its chemical identity.

Unprecedented energy storage in metal-organic complexes via constitutional isomerism - Kottaichamy, Alagar Raja; Deebansok, Siraprapha; Deng, Jie; Nazrulla, Mohammed Azeezulla; Zhu, Yachao; Bhat, Zahid Manzoor; Devendrachari, Mruthyunjayachari Chattanahalli; Vinod, Chathakudath Prabhakaran; Kotresh, Harish Makri Nimbegondi; Fontaine, Olivier; Thotiyl, Musthafa Ottakam (Chemical Science, 2023)
The essence of any electrochemical system is engraved in its electrical double layer (EDL), and we report its unprecedented reorganization by the structural isomerism of molecules, with a direct consequence on their energy storage capability. Electrochemical and spectroscopic analyses in combination with computational and modelling studies demonstrate that an attractive field-effect due to the molecule's structural-isomerism, in contrast to a repulsive field-effect, spatially screens the ion-ion coulombic repulsions in the EDL and reconfigures the local density of anions. In a laboratory-level prototype supercapacitor, those with beta-structural isomerism exhibit nearly 6-times elevated energy storage compared to the state-of-the-art electrodes, by delivering similar to 535 F g(-1) at 1 A g(-1) while maintaining high performance metrics even at a rate as high as 50 A g(-1). The elucidation of the decisive role of structural isomerism in reconfiguring the electrified interface represents a major step forward in understanding the electrodics of molecular platforms.

Ligand isomerization driven electrocatalytic switching - Kottaichamy, Alagar Raja; Nazrulla, Mohammed Azeezulla; Parmar, Muskan; Thimmappa, Ravikumar; Devendrachari, Mruthyunjayachari Chattanahalli; Vinod, Chathakudath Prabhakaran; Volokh, Michael; Kotresh, Harish Makri Nimbegondi; Shalom, Menny; Thotiyl, Musthafa Ottakam (ANGEWANDTE CHEMIE-INTERNATIONAL EDITION, 2024)
Keywords: Catalysts; CO2 reduction; O-2 REDUCTION; oxygen reduction